Evaluation Of Sociological Study On Intercaste And Interreligious Marriage With Special Reference To West Bengal (Journal of Namibian Studies : History Politics Culture, 2023)
A man and woman are connected in a system of reciprocal duties and rights necessary for a family to function through marriage, which is a social institution or set of social conventions that has traditionally legitimised their relationship. Marriage is a social compact that binds two people together legally, economically, and emotionally. It is a formal connection between two people. Inter-caste is the existence of our association with two or more castes. Inter-caste marriage happens when individuals of lower and upper castes marry. Interreligious is defined as involving two or more religious groups. Interfaith unions are not dependent on the individuals involved. In this article, evaluation of sociological study on inter-caste and interreligious marriage with special reference to West Bengal has been discussed.